The relationship between dental caries with asthma, disease duration, and type of medications in the Azar cohort population - Katayoun Katebi; Saba Ashkannejhad; Zeinab Mahboobi; Elnaz Faramarzi; Nasrin Sharififard (BMC Oral Health)
Abstract Introduction Due to the high prevalence of asthma worldwide, paying attention to oral health is important. This study explores the relationship between DMFT (decayed, missing, and filled teeth) and asthma, disease duration, and related medications in the Azar cohort population. Methods and materials In this cross-sectional analytical study, the part of the data related to asthma, disease duration, type of medications, and DMFT were extracted from the Azar cohort study. Azar cohort started among 15,006 adults (35–70 years old) in 2014 in the northwest of Iran. In the present study, all 538 asthmatic people in Azar cohort population included in asthma group and 1076 of non-asthmatic people included in the control group. The outcome variable was DMFT, D, M and F. A negative binomial with loglink was used to adjust the effect of confounding variables in regression models. Results Among the asthmatics, 28.3% were using anti-asthmatic medications. In 38.3% of the asthmatic group, the disease duration was ten years or more. In the asthmatic group, the mean DMFT was 23.15 ± 8.67, and the greatest section of the DMFT was related to M component. The relationship of DMFT and M component with asthma, disease duration, and medication were insignificant but D component showed significant relationship with asthma. Conclusion It can be assumed that the history of asthma does not have an effective role in DMFT index and M component in adults but decayed teeth were higher in asthmatics.